From Theory to Performance: Engaging With Foucault Through Arts-Based Research - Bhattarai, Ajit P. (Art/Research International)

(untitled) (University of Alberta, 2026)
In this article, I discuss how arts-based research (ABR) and the concept of "writing as inquiry" were used to engage with some of Michel Foucault’s ideas. As a non-traditional student returning to academia after a professional break, I initially struggled with traditional methods of reading and analyzing theoretical texts. Therefore, I turned to ABR to engage with Foucault’s work and was able to successfully engage with it. This manuscript focuses on a play that uses dialogue to explore concepts such as postmodernism, metanarratives, and Foucault’s theories in an accessible manner. Grounded in the principles of ABR, the play highlights the potential ways artistic representation can serve as both a method of inquiry and a tool for making theoretical ideas more relatable. The article demonstrates that ABR can provide an effective means of exploring theory, especially for non-traditional students, facilitating engagement and reflection.